KEBIJAKAN KOMUNIKASI DI MADIUN (Studi Kasus Pembentukan Perda No. 11 Tahun 2011 Tentang Lembaga Penyiaran Publik Lokal Suara Madiun) - Nurhana Marantika (ETTISAL : Journal of Communication, 2016)
AbstractLocal Public Broadcasting Institution (LPPL) Suara Madiun Radio is a transformation from Government's Special Radio (RKPD). As stated in the PP No. 11, 2005 on the Implementation of Broadcasting of Public Broadcasting, article 55 regulates the organizers of radio broadcasting and operators of television broadcasting which are established or owned by the local governments that have been existed and in operation before the enactment of this Government Regulation and choose to become a Local Public Broadcasting, shall make adjustments to the provisions of government regulation in one (1) year from the enactment of this government Regulation. This study aims to look at the process of the formation of Government Regulation No. 11, 2011 on Local Public Broadcasting of Suara Madiun Radio as a legal system of LPPL Suara Madiun Radion. By using the case study method, this study found several verdicts such as: firstly, procedures non-conformity for the production of an academic text of Government Regulation No. 11 2011. Secondly, production process of this Government regulation is not in accordance with the procedure. Thirdly, there is a political interest in the establishment of LPPL Suara Madiun Radio.